Phospholipid-Rich DC-Vesicles with Preserved Immune Fingerprints: A Stable and Scalable Platform for Precision Immunotherapy - Ramon Gutierrez-Sandoval; Francisco Gutierrez-Castro; Natalia Muñoz-Godoy; Ider Rivadeneira; Adolay Sobarzo; Luis Alarcón; Wilson Dorado; Andy Lagos; Diego Montenegro; Ignacio Muñoz; Rodrigo Aguilera; Jordan Iturra; et al. (Biomedicines, 2025)
Despite the progress in cancer immunotherapy, therapeutic responses in solid tumors remain suboptimal due to the immunosuppressive nature of the tumor microenvironment (TME), limited immune cell infiltration, and inefficient delivery of immune-activating agents. Dendritic cell-based therapies possess strong immunological potential but face challenges in viability, standardization, and scalability. Likewise, exosomes and CAR-T cells are hindered by instability, production complexity, and limited efficacy in immune-excluded tumor settings. Objective: This study evaluates dendritic cell-derived vesicles (DC-Vesicles), embedded in a phospholipid-rich structural scaffold, as a multi-functional and scalable platform for immune modulation and therapeutic delivery. We aimed to assess their structural stability, immune marker preservation under clinical processing conditions, and potential to reprogram the TME. Methods and Results: DC-Vesicles were generated and analyzed using bottom-up proteomics via nanoLC–MS/MS on a timsTOF Pro 2 system under three conditions: fresh, concentrated, and cryopreserved. A consistent proteomic profile of over 400 proteins was identified, with cryopreserved samples retaining >90% of immune-relevant markers. Differential expression analysis confirmed stability of key immunological proteins such as HLA-A, QSOX1, ICAM1, NAMPT, TIGAR, and Galectin-9. No significant degradation was observed post-cryopreservation. Visualization through heatmaps, PCA, and volcano plots supported inter-condition consistency. In silico modeling suggested preserved capacity for M1 macrophage polarization and CD8+ T cell activation. Conclusions: DC-Vesicles demonstrate structural resilience and functional retention across storage conditions. Their cold-chain-independent compatibility, immune-targeting profile, and potential regulatory classification as Non-New Chemical Entities (NCEs) support their advancement as candidates for precision immunotherapy in resistant solid tumors.